Pengaruh Kebutuhan Mencari Variasi Dan Brand Image Terhadap Brand Switching Behavior Dengan Mediasi Kepuasan Konsumen (Studi Pada Pelanggan The Body Shop Di Indonesia) - Nyoman Selsa Mustika Putri; Baiq Handayani Rinuastuti; Lalu Edy Herman Mulyono (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
The goals of this research is to determine the effect of Variety Seeking and Brand Image on Brand Switching Behavior by mediating Customer. The population is consumers who have made purchases of other brands before The Body Shop at least 1 time, while the sample is 85 consumers using purposive sampling. This type of research is associative research. Processing data in this study using SmartPLS versi 4.0.0 software. Based on the results of the analysis, Variety Seeking affects Brand Switching Behavior, Variety Seeking affects Customer Satisfaction, Customer Satisfaction affects Brand Switching Behavior and Brand Image effect Customer Satisfaction, Variety Seeking has no significant affects on Brand Switching Behavior and Brand Image has no significant effect on Brand Switching Behavior. However, Customer Satisfaction is able to mediate between Variety Seeking and Brand Image on Brand Switching Behavior.